Input pelaksanaan kangaroo mother care pada berat lahir rendah di rumah sakit - Andi Kasrida Dahlan; Wiwik Kusumawati; Retno Mawarti (Universitas Aisyiyah Yogyakarta, 2017)
Abstract: The research was aimed to explain the implementation ofKMC on LBW input. The research was qualitative descriptive phenomenologystudy was conducted at Hospital Sawerigading Palopo with4 main informant midwife / nurse who has done KMC. Collecting datausing the technique of in-depth interviews, observation and documentation.Analysis of the data with models Miles and Huberman. The resultsof this study showed that there is a policy, but still lacking socializationrelated to the implementation of KMC mothers and families with babiesof low birth weight, lack of human resources training and infrastructuredo not meet the standards. Conclusion: The availability of input componentsKMC implementation is notmaximized.